PERSEPSI KONSUMEN TERHADAP BAURAN PEMASARAN USAHA O’CHICKEN DI KELURAHAN SUKA MAJU KECAMATAN SAIL KOTA PEKANBARU - Rona Dwi Hidayah; Yusmini Yusmini; Eliza Eliza (Fakultas Pertanian, Universitas Riau, 2020)
This study aimed to determine consumer perceptions of the marketing mix in the business of O'Chicken. Survey method used in this research and purposive sampling was used to get 50 business customers of O'Chicken as sample. This research took place at the O'Chicken business. Qualitative analysis was quantitatively used in this study. The results showed that consumer perceptions of the marketing mix of product variables, price, place, promotion and service got an average score of 4.25, categorized as very well. Indicators in the product variables are trademark, product packaging, product quality and service score average 4.27, categorized as very well. Indicators on price variables were affordability, price appropriateness with product quality, price competitiveness, price appropriateness with production and price benefits affect consumer purchasing power gets an average score of 4.42, categorized as very well. Indicators in place variables were access, visibility, spacious and safe parking lots and the environment gets an average score of 4.42, categorized very well. Indicators on promotional variables were sales promotion, public relations and mouth-to-mouth information scored an average of 3.77, good categorized. Indicators in service variables were services when product offerings, services in the sale of products and services when delivery of products sold with an average score of 4.35, categorized as very well.